2021
DOI: 10.1002/jia2.25668
|View full text |Cite
|
Sign up to set email alerts
|

Integration of mental health services into HIV healthcare facilities among Thai adolescents and young adults living with HIV

Abstract: Introduction To assess the burden of depression, anxiety and suicidality; and to determine the impact of integrated mental health and HIV services on treatment outcomes among Thai adolescents and young adults living with HIV (AYHIV). Methods A multicentre prospective cohort study was conducted among AYHIV (15 to 25 years), and age‐ and sex‐matched HIV‐uninfected adolescents and young adults (HUAY). The Patient Health Questionnaire 9‐item (PHQ‐9) and Generalized Anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…9,10 In contrast to the data in youth, there have been few studies addressing depression and anxiety in adolescents living with HIV in the Asian context, with only one recent study revealing the rate of significant anxiety or depressive symptoms at about 20%, comparable to the rate in HIV-uninfected youths. 11,12 Due to differences in stage of psychosocial development between youth and young adults, they have distinct developmental tasks resulting in unique psychological and emotional changes. We hypothesized that the factors associated with depression and anxiety in the two groups may be different.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In contrast to the data in youth, there have been few studies addressing depression and anxiety in adolescents living with HIV in the Asian context, with only one recent study revealing the rate of significant anxiety or depressive symptoms at about 20%, comparable to the rate in HIV-uninfected youths. 11,12 Due to differences in stage of psychosocial development between youth and young adults, they have distinct developmental tasks resulting in unique psychological and emotional changes. We hypothesized that the factors associated with depression and anxiety in the two groups may be different.…”
Section: Introductionmentioning
confidence: 99%
“…Prior study of suicidality among AYA affected by HIV has found mixed results. Three cross‐sectional studies (from England, Thailand and South Africa) found no differences in suicide risk between AYALPHIV versus those without HIV [ 46 , 47 , 48 ]. Conversely, our current and prior work in the United States [ 50 ] and a study in Rwanda [ 49 ] both found an increased risk of suicidality among AYALPHIV compared to AYA without HIV.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis found that PLWHIV, median age 39 years, had a 100‐fold higher risk of dying by suicide than people not living with HIV, with an even higher risk for people living with AIDS [ 42 ]. While risk factors for suicide in the general population of AYA are well documented [ 43 , 44 , 45 ], few studies have examined suicidality among AYA living with perinatally acquired HIV (AYALPHIV) [ 24 ] and those that have showed mixed results [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Professional support where available 70 Support healthcare staff to understand mental health 20 PRIME modelintegration into primary care 71 Routine mental health screening 72,73 Training healthcare staff in mhGAP 71,74 Simple, immediate referral systems 20 There is emerging evidence of effective mental health services for adolescents living with HIV, including interventions promoting positive mental health or preventing onset of mental health disorders, as well as broader-based psychosocial interventions aimed at promoting adherence and engagement in care, or reducing risk behaviour. 75 A meta-analysis of psychosocial interventions for adolescents living with HIV found small to moderate benefits on improved adherence to ART and reduced viral load, 76 leading to a strong recommendation of psychosocial interventions for young people living with HIV.…”
Section: Initial Evidence For Digital Deliverymentioning
confidence: 99%
“…104 In contexts where there are human and financial resources available, integrating screening and referral to qualified psychiatric or psychological staff is beneficial for adolescents experiencing acute distress. 70 However, there remains severe scarcity of psychiatric professionals in the Global South, with 1.4 mental health workers per 100,000 population in the African WHO region, 105 and almost no adolescent inpatient wards. An innovative model for addressing this generalised mental health gap is the Programme for Improving Mental health care (PRIME), 71 which worked with Ministries of Health and partners in five LMIC countries to integrate evidence-based psychosocial and pharmacological interventions into existing primary healthcare systems, using WHO's mhGAP guidelines.…”
Section: Panel 2: Cost-effectiveness Of Integrating Mental Health Car...mentioning
confidence: 99%